PEMINGSANAN (STUNNING): HALALKAH UNTUK PRA-PENYEMBELIHAN HEWAN HALAL ? - Eko Saputro (Jurnal Kewidyaiswaraan, 2021)
The world's Muslim population has exceeded two billion people, the terms and conditions of halal meat for the Muslim community are of great importance both ethically and economically. Since 1976, the Indonesian Ulema Council (ajelis Ulama Indonesi, MUI) has legalized the method of stunning pre-slaughter of halal animals through an MUI Fatwa dated 24 Shawwal 1396 H / October 18, 1976. with the doctrines of the Prophet Muhammad SAW and meet the requirements of the provisions of the Shari'a and the law is legal and halal (lawful), and therefore, it is hoped that the Muslims will not doubt it. However, it has not been explained in the fatwa regarding the various methods and existing stunning equipment that meet the halal requirements for the halal slaughter of various halal animals. This has sparked debate among Muslims as well as animal welfare activists. A very important and critical operation at the abattoir is the transformation of a halal animal into a healthy piece of halal meat for human consumption through a ritual process of halal slaughter. This article does not discuss the debate about halal slaughter without stunning being inhumane or slaughter with stunning being controversial from an Islamic point of view. This article discusses the slaughter, stunning and welfare of animals by considering the requirements of Islamic law and animal welfare laws. From the point of view of animal welfare standards, a number of issues have been raised regarding halal slaughter without stunning, in particular, regarding the stress-required laying method and unconscious latency. This paper discusses various methods of halal pre-slaughter stunning stunning various halal animals that have been permitted by Islamic authorities.